2021
DOI: 10.1108/ijchm-01-2021-0109
|View full text |Cite
|
Sign up to set email alerts
|

Why do hotel interns stay in the hospitality and tourism industry? An interactionist perspective of organizational socialization

Abstract: Purpose Promoting interns’ organizational socialization has become an urgent concern for the hotel industry. Building on career construction theory, this study aims to use a time-lagged design to investigate the interrelationships among perceived organizational support (POS), psychological capital and organizational socialization and their consequent effects on interns’ intention to stay in the hotel industry. Design/methodology/approach Panel data were obtained in three waves from hotel interns from 21 upsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 82 publications
1
10
0
Order By: Relevance
“…This adds to the limited knowledge of factors that are associated with restaurant employees’ turnover intention in the context of a global crisis by suggesting that employees’ job stress could transfer into the decision of leaving the industry altogether through an intensified intention to leave the current organization. Consistent with previous research (Zhou et al , 2022), employees’ organizational-level outcomes are crucial links between personal/organizational factors and their long-term career choices. Specifically, this study broadens the scope of organizational outcomes proposed in previous research (e.g.…”
Section: Discussionsupporting
confidence: 86%
“…This adds to the limited knowledge of factors that are associated with restaurant employees’ turnover intention in the context of a global crisis by suggesting that employees’ job stress could transfer into the decision of leaving the industry altogether through an intensified intention to leave the current organization. Consistent with previous research (Zhou et al , 2022), employees’ organizational-level outcomes are crucial links between personal/organizational factors and their long-term career choices. Specifically, this study broadens the scope of organizational outcomes proposed in previous research (e.g.…”
Section: Discussionsupporting
confidence: 86%
“…job responsibility and role conflict, ambiguity and overload). Job security, insecurity, psychological safety, job burnout and career plan are also important (Zhou et al , 2021), Studies have further identified various job profile variables as moderators and/or control factors including experience, job position, tenure, type of contract and working hours.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, negative experiences in early interactions with veterans can drive newcomers to quit (Josefowitz and Gadon, 1989). Newcomers in the hospitality sector have to quickly adjust and understand their roles to smoothly deliver services (Zhou et al, 2021a) and may experience workplace bullying from veterans for failing to do so. Bullying further leads to newcomers' job dissatisfaction and causes burnout (Alexander et al, 2012), thereby increasing TIs.…”
Section: Reported Workplace Bullying and Newcomer Turnover Intentionsmentioning
confidence: 99%